Pendampingan Penyusunan Unique Selling Point di Desa Wisata Borobudur, Kabupaten Magelang - Sinuraya, Suci Iriani; Wismaningtyas, Tri Asih (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The presence of Borobudur as one of the five Super Priority Areas (DSP) Tourism development needs to be carried out by participating in developing the surrounding area: first, so that the duration of tourist visits in Borobudur can be longer because there are other geographically integrated magnets that can be visited, and secondly so that it is sustainable If a tourist destination can maintain its presence, the community around the location of the Borobudur Temple destination must benefit from the existence of that destination. The existing Borobudur Temple is surrounded by a number of villages which support it, so the Directorate of Regional Tourism Destination Development I of the Ministry of Tourism and Creative Economy then agreed that 3 villages around Borobudur Temple should be prioritized for developing tourist villages, namely Karanganyar Tourism Village, Karangrejo Tourism Village and Borobudur Village. Borobudur Village itself has responded to this business opportunity with plans to develop the unique potential in each hamlet through the Thematic Village Program, and of the 21 new hamlets, 6 hamlets have started to discover potential and develop it, 15 other hamlets are still in the process of exploring potential. The Tidar Magelang University Community Service Team responded to this situation and provided education about the need to develop a tourist village based on the unique potential that exists in the village. The uniqueness of the product/service must differentiate it from products from other tourist villages and be in line with what tourists expect. This understanding is useful for the management of a tourist village so that they can focus on its development and have an optimal impact on improving the welfare of the surrounding community.